Psychological Adjustment of Spanish Parents and Premature Children - Cuéllar-Flores, Isabel; Sierra-García, Purificación; Valle Trapero, Mercedes; Martínez, Selene; Martínez-Orgado, José Antonio (Revista de Psicología, 2021)
To date there have been few studies in Spain and Latin America that address the psychological adjustment of premature infants. This paper examines the psychological adjustment of children and some factors relevant to it, in a sample of Spanish premature children. Participants: 29 minors (Mean age = 36.2 months, SD = 1.42) with a history of prematurity. 51.7% were girls. Instruments: A sociodemographic survey, the Strengths and Difficulties Questionnaire (SDQ) and the Parental Stress Scale (PSS) were used. Results: Between 71.4 and 82.1% of the children obtained scores considered normal in the SDQ, in 50% of them, their parents indicated the existence of some negative impact. There are no statistically significant relationships between the SDQ scales and the neonatal variables. Being Spanish, having higher education and being active was related to a better psychological adjustment in children. Parental stress was associated with a worse adjustment. Conclusions: The study of the strengths and psychological adjustment of parents and children in prematurity is of special importance to know, prevent and intervene on the well-being of this population.